Molecular Evidences of a Hidden Complex Scenario in Leporinus cf. friderici - Silva-Santos, Rosane; Ramirez, Jorge L.; Galetti, Pedro M.; Freitas, Patrícia D. (Frontiers in Genetics, 2018)
The megadiversity of the Neotropical ichthyofauna has been associated to recent diversification processes, reflecting in subtle or lacking morphological differentiation between species, challenging the classical taxonomic identification. Leporinus friderici occurs in several river basins of South America, and its nominal taxonomic validity has been questioned. Its wide distribution within Brazilian Shield suggests that this species could be genetically structured among the hydrographic basins, despite a sharp morphological similarity. In this study, we performed phylogenetic analyses, based on three nuclear (RAG1, RAG2 and Myh6) and two mitochondrial (COI and Cytb) markers, in specimens morphologically similar to L. friderici and related species from different hydrographic basins in South America. Our phylogenetic tree identified four well-supported clades, point out to the existence of taxonomic inconsistencies within this fish group. A clade named L. cf. friderici sensu stricto included eight MOTUs (Molecular Operational Taxonomic Units) recently diversified in the Brazilian Shield basins. These results were also confirmed by a single-gene species delimitation analysis. It is suggested that this clade includes a species complex, characterizing taxonomic uncertainties. Another clade recovered only L. friderici from the Suriname rivers, validating this nominal species in its type locality. A third no-named clade, characterized by deeper species divergence, recovered five different nominal species interleaved with other undescribed forms previously also recognized as L. cf. friderici, indicating taxonomic errors. The fourth clade only included L. taeniatus. Our results showed a complex scenario involving the morphotype L. cf. friderici, and allowed us to address aspects related to evolutionary diversification of this fish group and historical processes involved with, highlighting the importance of revealing hidden biodiversity for the taxonomy and conservationist action plans of these fish.